2001
DOI: 10.1038/sj.bjp.0704115
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of the prejunctional modulation of cholinergic neurotransmission during chronic granulomatous inflammation of the mouse ileum

Abstract: 1 The e ect of chronic granulomatous in¯ammation of the intestine was studied on the prejunctional modulation of cholinergic nerve activity in the mouse ileum. 2 Contractions to carbachol (0.01 ± 0.3 mM) and to electrical ®eld stimulation (EFS, 0.25 ± 8 Hz) of enteric neurons were higher in in¯amed ileum as compared to control ileum. However, when the neurally-mediated contractions to EFS were expressed as percentage of the direct smooth muscle contraction to carbachol, the responses to EFS were similar in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Contractility of smooth muscle to cholinergic or tachykinergic stimuli is increased in the early stages and decreased in the later stages of inflammation (38,39), and contractility following electrical neuronal stimulation in the inflamed gut is increased (40). The electrophysiological changes in the distal colon, as used in this study, show increased smooth muscular excitability, leading to the occurrence of spontaneous spiking activity.…”
Section: Discussionmentioning
confidence: 82%
“…Contractility of smooth muscle to cholinergic or tachykinergic stimuli is increased in the early stages and decreased in the later stages of inflammation (38,39), and contractility following electrical neuronal stimulation in the inflamed gut is increased (40). The electrophysiological changes in the distal colon, as used in this study, show increased smooth muscular excitability, leading to the occurrence of spontaneous spiking activity.…”
Section: Discussionmentioning
confidence: 82%
“…The A 2B AR has been identified in various biological functions, including vasodilation, inhibition of endothelial smooth muscle growth, allergy, and inflammation reactions (13, 17, 2428). In the present study, we investigated the functional importance of the enteric neuronal A 2B AR in modulating distal colonic motility.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed smooth muscle relaxation [28], others showed contraction [29]. One study showed that DMPP reduces the bronchomotor tone in cats [19].…”
Section: Discussionmentioning
confidence: 99%